Copper ion detection kit as well as preparation method and application thereof

By designing copper ion detection materials based on AIE materials, using the combination of TPE groups and recognition groups, the portability and detection range limitation of existing copper ion detection methods are solved, and the effect of high sensitivity and real-time detection is achieved.

CN119861057AActive Publication Date: 2025-04-22SUN YAT SEN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510091817.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing copper ion detection methods have problems such as high equipment cost, complex operation, long detection time, poor portability and inability to achieve real-time detection on site. In addition, traditional fluorescent probes are fluorescently quenched in high concentration or aggregation state, and the detection range is limited.

Method used

Using copper ion detection materials designed based on aggregation-induced luminescence (AIE) material, small-molecular and polymer AIE copper ion detection materials are formed through the combination of TPE groups and recognition groups, which can significantly increase the fluorescence intensity in a high moisture content system and achieve quantitative detection by coordination between recognition groups and copper ions.

Benefits of technology

It realizes high sensitivity copper ion detection at any concentration, expands the detection range, simplifies operations, reduces costs, and has the ability to detect in real time on-site.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119861057A_ABST
    Figure CN119861057A_ABST
Patent Text Reader

Abstract

The invention discloses a copper ion detection kit as well as a preparation method and application thereof. The kit comprises a copper ion detection material based on aggregation-induced emission, and the copper ion detection material is composed of tetraphenyl ethylene (TPE), a copper ion recognition group and a component containing or not containing a hydrophilic polymer material. According to the copper ion detection kit, the problem of concentration quenching does not exist in detection of copper ions, and the detection range of the copper ions can be remarkably expanded; the high-molecular chain segment contained in the copper ion detection material in the kit can promote the aggregation of the copper ion detection material through additional acting force so as to have stronger fluorescence emission, and due to the change of the aggregation mode, the copper ion detection material has higher sensitivity to copper ions; the invention provides a copper ion detection kit with excellent selectivity, detection limit and detection range. The preparation is simple, the cost is low and the operation is convenient. The copper ion detection kit disclosed by the invention has practical application value in the fields of detection of copper ions in in-vitro clinical samples and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper ion detection, and specifically relates to a copper ion detection kit and a preparation method and application thereof. Background Art

[0002] As an essential trace element for the human body, copper plays a key role in many biological processes such as mitochondrial respiration, antioxidant activity, tissue integrity, autophagy and immune regulation. Too much or too little copper is harmful. An imbalance in copper homeostasis may lead to changes in various physiological functions and the occurrence of various diseases, and is closely related to the occurrence and development of tumors. Therefore, if the abnormal concentration of copper ions can be monitored in time through accurate and sensitive copper ion detection methods, early detection and early treatment can prevent or delay the development of the disease in time. For example, high concentrations of copper in serum and urine are associated with diseases such as cancer, liver disease, acute and chronic infections, and rheumatoid arthritis; the detection of copper concentration can indicate early signs of Alzheimer's disease; hereditary Wilson's disease can be detected by evaluating the copper concentration in urine.

[0003] Traditional copper ion detection methods mainly include atomic absorption spectroscopy, atomic emission spectroscopy, inductively coupled plasma mass spectrometry and electrochemical analysis. However, these detection methods that rely on large fixed instruments have the following disadvantages: expensive instruments and equipment, high operating costs, long detection time, cumbersome procedures, low portability, need for professional technicians to operate, and inability to achieve on-site real-time detection, etc., and have low clinical popularity. Therefore, there is an urgent need to develop an effective detection method that is low-cost, simple, fast, and highly portable.

[0004] In recent years, the fluorescence method for detecting copper ions has significant advantages, such as low equipment cost, simple operation, fast analysis speed, good reproducibility, and high sensitivity. However, the performance of fluorescent probes depends largely on the fluorophore used. Traditional fluorescent dyes such as coumarin and rhodamine usually have strong emission only in dilute solutions. When they are in high concentrations or aggregated states, the strong π-π stacking interaction often triggers aggregation-induced emission quenching (ACQ), resulting in the weakening or quenching of dye fluorescence. Therefore, organic fluorescent probes designed based on such dyes are usually only used at low concentrations, which reduces the detection range of copper ions.

[0005] In stark contrast to ACQ, fluorescent materials with aggregation-induced emission (AIE) have strong fluorescence emission when in high concentration or aggregated state due to the restriction of intramolecular motion. AIE fluorescent materials can be used at any concentration without considering fluorescence quenching, which is conducive to their use in water or high water content environment. AIE materials also exhibit significant photophysical properties, such as large Stokes shift and excellent photostability. Based on the above characteristics, AIE materials are widely used in the field of metal ion detection. Summary of the invention

[0006] In order to overcome the shortcomings and deficiencies of the prior art, the object of the present invention is to provide a copper ion detection kit with both selectivity, detection limit and detection range. The copper ion detection materials based on AIE contained in the copper ion detection kit disclosed in the present invention are divided into small molecule AIE copper ion detection materials and polymer AIE copper ion detection materials, both of which can be used as highly sensitive fluorescent probes in high water content systems. Copper ions can significantly affect the fluorescence of the material, significantly increase the solubility of the AIE material by coordinating with the copper ion recognition group therein, destroy the nano-aggregated luminophore formed by the material and cause the fluorescence change of the system, and realize the quantitative detection of copper ions by the degree of change of fluorescence. The polymer segment in the polymer AIE copper ion detection material can promote the aggregation of the AIE material through additional forces and emit stronger fluorescence. At the same time, due to the change in aggregation mode, the polymer AIE copper ion detection material has a higher sensitivity to copper ions, further expanding the detection range of copper ions.

[0007] Another object of the present invention is to provide a preparation method and application of the copper ion detection kit based on the above-mentioned aggregation-induced luminescence copper ion detection material.

[0008] The purpose of the present invention is achieved based on the following technical solutions:

[0009] A copper ion detection kit, characterized in that it comprises a copper ion detection material based on aggregation-induced luminescence, which is composed of a TPE group with aggregation-induced luminescence performance as a fluorophore, a recognition group with strong selective recognition ability for copper ions, and a component containing or not containing a hydrophilic polymer material, and has a structure shown in general formula I:

[0010] General formula Ⅰ:

[0011] Among them, the fluorophore TPE is ;

[0012] X is -CH2-, -CH2OCO-, NH, -NHCO-, O, -OCO- or -CONH-;

[0013] L is a linking group, including an alkylene group or an alkoxy group;

[0014] G is a hydrophilic polymer material, including but not limited to the following polymers: hyaluronic acid, carboxymethyl chitosan, chondroitin sulfate, γ-polyglutamic acid, polyvinyl alcohol;

[0015] R is a recognition group, which is generally an organic multidentate ligand that can coordinate with copper ions, and contains one of the coordination groups such as N, O, S, or any combination thereof.

[0016] The fluorophore TPE is partially or completely substituted by -XR and -XLG, and has a structure shown in the general formula II, and R1, R2, R3, and R4 are four substitution positions that can be substituted. Among them, R1, R2, R3, and R4 are partially or completely substituted by -XR, and the unsubstituted position is H, which is a small molecule AIE copper ion detection material; or R1 is substituted by -XLG, and R2, R3, and R4 are partially or completely substituted by -XR, and the unsubstituted position is H, which is a high molecular AIE copper ion detection material.

[0017] General formula II:

[0018] In some specific embodiments of the present invention, the R1, R2, R3, and R4 positions are preferably substituted by -XR, and the unsubstituted position is H; or the R1 position is substituted by -XLG, and the R4 position is preferably substituted by -XR, and the unsubstituted R2 and R3 positions are H.

[0019] L is a connecting group, including an alkylene group or an alkoxy group. Among them, the alkylene group is -(CH2) n -, alkenylene, alkynylene, cycloalkylene or heteroarylene, or any combination thereof; alkoxy is -(CH2) n CO-、-(OCH2CH2O) n -、-(CH2CH2O) n -、-(OCH2CH2OCH2) n -、-(CH2CH2OCH2) n -、-(CH2CH2OCH2CH2) n - or any combination thereof, wherein n represents a natural number from 1 to 20.

[0020] In some specific embodiments of the present invention, the alkylene group is preferably -(CH2) n -, the alkoxy group is preferably -(OCH2CH2O) n -、-(CH2CH2O) n -、-(OCH2CH2OCH2) n -、-(CH2CH2OCH2)n -、-(CH2CH2OCH2CH2) n - or any combination thereof, wherein n represents a natural number from 1 to 6.

[0021] R is a recognition group for copper ions, and its structural characteristics are as follows:

[0022] General formula III:

[0023] Wherein, Z is N or CH, and n represents a natural number from 0 to 20;

[0024] R5 and R6 can be the same or different coordinating groups containing N, O, S electron donors, etc., or one can be H and the other can be a multidentate coordinating group, including but not limited to the following groups:

[0025] , , , , , ;

[0026] “ ” represents the place where the substituent is attached.

[0027] In some specific embodiments of the present invention, the copper ion recognition group R is preferably the following group:

[0028] , , , .

[0029] In some specific embodiments of the present invention, X is preferably -CH2- or -CONH-; the hydrophilic polymer material G is preferably hyaluronic acid, carboxymethyl chitosan, or γ-polyglutamic acid.

[0030] In some specific embodiments of the present invention, a small molecule copper ion detection material is obtained in which R1, R2, R3, and R4 are substituted by -XR and the unsubstituted position is H, referred to as TPE-DPA, wherein:

[0031] X is -CONH-, R is .

[0032] In some specific embodiments of the present invention, a small molecule copper ion detection material is obtained in which R1, R2, R3, and R4 are substituted by -XR and the unsubstituted position is H, referred to as TPE-DPA-1, wherein:

[0033] X is -CH2-, R is .

[0034] In some specific embodiments of the present invention, a polymer copper ion detection material is obtained in which R1 is substituted by -XLG, R4 is substituted by -XR, and R2 and R3 are not substituted by H, which is referred to as HA-TPE-DPA, wherein X is -CONH- and G is hyaluronic acid: , L is -(CH2)6-, R is .

[0035] The above-mentioned copper ion detection materials based on aggregation-induced luminescence all have strong fluorescence emission in high water content systems. When copper ions exist in the system, the recognition groups in the material coordinate with the copper ions to significantly increase their water solubility, destroy the nano-aggregate luminophores formed by the material and cause changes in the fluorescence of the system. Quantitative detection of copper ions is achieved through the degree of fluorescence change.

[0036] The copper ion detection material based on aggregation-induced luminescence provided by the present invention can be prepared according to the following method: first, a TPE with a carboxyl group or a TPE halogenated at the benign position is synthesized, and a small molecule AIE copper ion detection material is obtained by an amide reaction or a substitution reaction with a recognition group R; the TPE with a carboxyl group or the TPE halogenated at the benign position is first connected to one end of a connecting group L and a recognition group R by an amide reaction, an esterification reaction or a substitution reaction, and then the other end of the connecting group L is modified on a hydrophilic polymer material G to obtain a polymer AIE copper ion detection material.

[0037] The copper ion detection kit provided by the present invention can be applied to, including but not limited to, clinical 24-hour urine copper detection, serum copper content detection, tissue copper content detection, cell copper content detection, and sewage copper content detection, and the application forms include but are not limited to the use of a multifunctional microplate reader, a fluorescence spectrometer, and taking pictures to identify RGB according to the fluorescence color.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The copper ion detection kit provided by the present invention can be used at any concentration without considering fluorescence quenching, and can be used as a highly sensitive fluorescence detection probe in a high water content system. It also has a wide response range for copper ion detection, providing a copper ion detection kit with excellent selectivity, detection limit and detection range, which is expected to be used for copper ion detection in both copper excess and copper deficiency diseases.

[0040] (2) The copper ion detection kit provided by the present invention has a novel detection mechanism for copper ions. After the recognition group of the copper ion detection material based on aggregation-induced luminescence is coordinated with the copper ion, its solubility is significantly increased, resulting in a change in the fluorescence of the system, thereby achieving quantitative detection of copper ions. It is also proposed that the aggregation of the aggregation-induced luminescence material can be promoted by introducing a polymer chain segment, resulting in a change in the aggregation pattern, thereby further improving the detection sensitivity of copper ions, providing a new method and new idea for the field of copper ion detection technology.

[0041] (3) Compared with the traditional copper ion detection technology with high cost, complicated procedures, low portability, and inability to achieve on-site real-time detection, the copper ion detection kit provided by the present invention is simple to prepare, and has the advantages of simple operation, rapidity, high sensitivity, and ability to achieve real-time detection of copper ions. It has practical application value in copper ion detection in the fields of medicine and environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The specific implementation examples of the present invention are further described in detail below in conjunction with the accompanying drawings, wherein:

[0043] Figure 1 This is the H NMR spectrum of TPE-DPA in Example 1.

[0044] Figure 2 This is the H NMR spectrum of TPE-DPA-1 in Example 2.

[0045] Figure 3 This is the H NMR spectrum of HA-TPE-DPA in Example 3.

[0046] Figure 4 The fluorescence spectra of TPE-DPA in Example 4 in systems with different water contents (0-95%) (A) and the fluorescence intensity change curve at 460 nm (B) are shown.

[0047] Figure 5 The TPE-DPA and different equivalents of Cu in Example 5 2+ Fluorescence spectrum after mixing (A) and fluorescence intensity change curve at 460 nm (B); TPE-DPA-1 and different equivalents of Cu 2+ Fluorescence spectrum after mixing (C) and fluorescence intensity change curve at 460 nm (D).

[0048] Figure 6 The results of investigating the metal ion specificity of TPE-DPA in Example 6 are shown in FIG.

[0049] Figure 7 is TPE-DPA and Cu in Example 7 2+ UV-visible absorption spectra before and after mixing (+ indicates 0.22μm water membrane filtration)

[0050] Figure 8 : This is a graph showing the fluorescence intensity change at 460 nm of different concentrations of HA-TPE-DPA (3 k-10 k) and TPE-DPA-C6 in Example 8.

[0051] Fig. 9 The fluorescence intensity of (A) TPE-DPA and (B) HA-TPE-DPA at 460 nm and Cu 2+ Concentration standard curve.

[0052] Fig.10 This is a comparison of the results of HA-TPE-DPA and ICP-MS testing of 24-hour urine copper content in Wilson disease model rats in Example 10. DETAILED DESCRIPTION

[0053] The preferred embodiments are explained in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0054] Example 1: Preparation of small molecule AIE copper ion detection material TPE-DPA

[0055]

[0056] At room temperature, 0.3 g (0.8 mmol) of 4-(1,2,2-triphenylvinyl)benzoic acid, 0.232 g (0.96 mmol) of DPA-NH2, 0.183 g (0.95 mmol) of EDCI and 0.117 g (0.96 mmol) of DMAP were dissolved in 20 mL of dichloromethane and stirred at room temperature for reaction. The reaction was monitored by TLC. After the reaction was completed, the reaction solution was washed with 0.5 M HCl (30 mL), water (60 mL × 2), and saturated brine (60 mL × 2) in sequence. The organic phase was collected, dried over anhydrous sodium sulfate, and concentrated. The target product TPE-DPA was purified by preparative thin layer chromatography (dichloromethane: methanol = 9:1) to obtain a light yellow solid.

[0057] Example 2: Preparation of small molecule AIE copper ion detection material TPE-DPA-1

[0058]

[0059] Under nitrogen protection, 0.25 g (0.59 mmol) of 1,1,2-triphenyl-2-(4-bromomethylphenyl)ethylene and 0.234 g (1.17 mmol) of 2,2'-dipicolylamine were dissolved in 25 mL of anhydrous tetrahydrofuran, and 0.163 g (1.18 mmol) of potassium carbonate was added. The reaction was stirred at room temperature until the reaction of the raw materials was completed by TLC monitoring. After the reaction was completed, the reaction solution was filtered and concentrated, and then redissolved with 60 mL of dichloromethane, and then washed with water (100 mL × 2) and saturated brine (100 mL × 2). The organic phase was dried over anhydrous sodium sulfate and filtered. The filtrate was concentrated and purified by preparative thin layer chromatography (dichloromethane: methanol = 22:1) to obtain the target compound TPE-DPA-1 as a brown oil.

[0060] Example 3: Preparation of polymer AIE copper ion detection material HA-TPE-DPA

[0061]

[0062] 1) Preparation of intermediate compound TPE-C6: 0.5 g (1.19 mmol) 1,2-di(4-carboxyphenyl)-1,2-stilbene, 0.257 g (1.18 mmol) tert-butyl N-(6-aminohexyl)carbamate, 0.543 g (1.43 mmol) HATU and 0.117 g (2.38 mmol) DIPEA were dissolved in 25 mL N,N-dimethylformamide at room temperature and stirred at room temperature for 4 h. After the reaction was completed, the reaction solution was diluted with 150 mL ethyl acetate and extracted with water (250 mL × 3). The organic phase was collected and washed with 0.4 M HCl (60 mL) and saturated brine (120 mL × 2), dried over anhydrous sodium sulfate and concentrated, and purified by column chromatography (dichloromethane: methanol = 20:1) to obtain compound TPE-C6 as a yellow oil.

[0063] 2) Preparation of intermediate compound TPE-DPA-C6-Boc: 0.37 g (0.6 mmol) TPE-C6, 0.174 g (0.72 mmol) DPA-NH2, 0.138 g (0.72 mmol) EDCI and 0.09 g (0.72 mmol) DMAP were dissolved in 25 mL dichloromethane at room temperature and stirred overnight at room temperature. After the reaction was completed, the reaction solution was washed with 0.4 M HCl (30 mL), water (60 mL × 2) and saturated brine (80 mL × 2) in sequence, and the organic phase was collected, dried over anhydrous sodium sulfate and concentrated to obtain compound TPE-DPA-C6-Boc as a brown oil.

[0064] 3) Preparation of intermediate compound TPE-DPA-C6: TPE-DPA-C6-Boc was dissolved in (20 v / m) dichloromethane at room temperature, the reaction solution was placed in an ice bath at 0 °C and stirred, and (5 v / m) TFA was slowly added dropwise. After the addition was completed, the reaction was maintained under ice bath conditions for 30 min, and then heated to room temperature and stirred for 2 h. After the reaction was completed, the reaction solution was adjusted to pH = 12 with 5% NaOH solution, the organic layer was separated, washed with saturated brine (30 mL × 2), dried over anhydrous sodium sulfate, and the organic solvent was evaporated and purified by preparative thin layer chromatography (dichloromethane: methanol: glacial acetic acid = 20:1:1) to obtain compound TPE-DPA-C6 as a yellow solid.

[0065] 4) Preparation of polymer HA-TBA: Disperse 1 g HA (3 k-10 k) in 40 mL 95% ethanol at room temperature, add 4 mL concentrated HCl, stir at room temperature for 1 h, let stand for 20 min, pour out the supernatant, keep the precipitate, and repeat the above steps 3 times. Take the precipitate and continue to wash with ethanol (500 mL × 3), centrifuge at 4000 rpm for 10 min to collect the remaining precipitate. Dissolve the precipitate in 100 mL pure water, adjust the solution pH = 7 with tetrabutylammonium hydroxide solution, transfer the solution to a freeze plate, and freeze-dry to obtain HA-TBA (3 k-10 k) as a white flocculent.

[0066] 5) Preparation of HA-TPE-DPA: At room temperature, 0.07 g HA-TBA (3 k-10 k) was dissolved in 20 mL N,N-dimethylformamide, and 0.13 g (0.17 mmol) TPE-DPA-C6, 0.022 g (0.17 mmol) DIC, 0.095 g (0.70 mmol) HOBT, 0.090 g (0.70 mmol) DIPEA and 0.022 g (0.17 mmol) DMAP were added to the reaction system, and stirred at room temperature for 36 h. After the reaction was completed, the reaction solution was transferred to a dialysis bag (Mw = 1000 Da), and dialyzed in a mixed system of (ethanol: water = 1:1) for 36 h, and then dialyzed in pure water for 36 h. After dialysis, the dialysate was transferred to a freezing plate and freeze-dried to obtain the polymer AIE copper ion detection material HA-TPE-DPA (3 k-10 k) as a light yellow flocculent.

[0067] Example 4: Verification of AIE properties of TPE-DPA

[0068] The AIE properties of TPE-DPA were investigated using a fluorescence spectrometer. TPE-DPA was dissolved in DMSO to prepare a 40 μM mother solution, and TPE-DPA was diluted to 2 μM with a mixed solution of ultrapure water and DMSO, so that the water content in the samples was 10%, 20%, 40%, 60%, 80%, 90%, and 95%, respectively. After standing for 30 min, the fluorescence emission spectrum of each sample was measured using a fluorescence spectrometer with the following parameters: excitation wavelength 320 nm, emission wavelength: 365 nm-650 nm. The fluorescence intensity value at 460 nm was plotted as a function of water content. The results are shown in Figure 4 As shown in the figure, when the water content of the system exceeds 60%, the fluorescence of TPE-DPA is greatly enhanced; when the water content reaches 95%, the fluorescence value at 460 nm is about 60 times that of the initial fluorescence. TPE-DPA retains the AIE properties of the TPE core and can be used as a highly sensitive fluorescent probe in high water content systems.

[0069] Example 5: Cu of TPE-DPA and TPE-DPA-1 2+ Responsiveness inspection

[0070] Fluorescence spectrometer was used to investigate the Cu 2+ Effect on the fluorescence properties of TPE-DPA. Dissolve CuCl2·2H2O in water to prepare a 400 μM stock solution. Dissolve TPE-DPA and TPE-DPA-1 in DMSO to prepare a 200 μM stock solution. Prepare samples according to the ratio of TPE-DPA:Cu = 1:0, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:2, where the concentration of TPE-DPA is 2 μM and the concentration of Cu is 2 μM. 2+ The corresponding concentrations were 0 μM, 0.4 μM, 0.8 μM, 1.2 μM, 1.6 μM, 2 μM, and 4 μM; the samples were prepared according to the ratio of TPE-DPA-1:Cu = 1:0, 1:0.1, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, and 1:2, where the concentration of TPE-DPA-1 was 2 μM and the concentration of Cu 2+ The corresponding concentrations were 0, 0.2, 0.4, 0.8, 1.2, 1.6, 2, and 4 μM, and the solvent system was 1% DMSO / 99% H2O. After each sample was vortexed and placed for 15 min, the fluorescence emission spectrum of each sample was measured using a fluorescence spectrometer with the following parameters: excitation wavelength: 320 nm, emission wavelength: 365 nm-650 / 600 nm. The fluorescence intensity value at 460 nm was plotted as a function of the ratio. The results are shown in Figure 2. Figure 5 As shown, with Cu 2+ As the addition ratio continued to increase, the fluorescence of TPE-DPA and TPE-DPA-1 solutions continued to decline, indicating that Cu 2+It can also significantly affect the aggregation effect of TPE-DPA and TPE-DPA-1, resulting in fluorescence quenching. Based on this characteristic, TPE-DPA and TPE-DPA-1 can be used as Cu 2+ Quenching type fluorescence detection probe to achieve Cu 2+ Sensitive detection.

[0071] Example 6: Investigation of Metal Ion Specificity of TPE-DPA

[0072] The metal ion specificity of TPE-DPA was investigated by fluorescence spectrometer. The following different metals: AgNO3, CaCl2, CoCl2·6H2O, CuCl2·2H2O, FeCl2, FeCl3·6H2O, KCl, MgCl2, NaCl, ZnCl2 were dissolved in water to prepare a 200 μM mother solution. TPE-DPA was dissolved in DMSO to prepare a 200 μM mother solution, and each sample was prepared according to the concentration of different metal ions of 2 μM and the concentration of TPE-DPA of 2 μM (the solvent system was 1% DMSO / 99% H2O). After each sample was vortexed and placed for 15 min, the fluorescence emission spectrum of each sample was measured by fluorescence spectrometer with the parameters as follows: excitation wavelength: 320 nm, emission wavelength: 365 nm-650 nm. The fluorescence intensity value at 460 nm was taken to plot the different metal ions. The results are shown in Figure 6 As shown, TPE-DPA has a great influence on Cu 2+ It has strong metal ion selectivity. Other metal ions have little effect on the fluorescence of TPE-DPA. It can be applied to Cu 2+ Specific detection.

[0073] Example 7: TPE-DPA and Cu 2+ Investigation of changes in UV absorption spectra before and after action

[0074] UV-visible absorption spectrometer was used to measure the 2+ The changes in the UV absorption spectrum before and after the action were investigated. Prepare 10 mM DMSO stock solution of TPE-DPA, prepare 10 mM aqueous stock solutions of CuCl2·2H2O, FeCl3·6H2O, CaCl2, and ZnCl2, add equal volumes of the above TPE-DPA and each metal ion stock solution to water until the final concentration is 100 μM (the final system is 1% DMSO / 99% H2O). After each sample was vortexed and allowed to stand for 15 min, the above samples were divided into two parts, one of which was not treated, and the other was filtered through a 0.22 μm water membrane, and the filtrate was collected. The UV-Vis absorption spectrum of each sample was measured using a UV-visible absorption spectrometer. The results are shown in Figure 7As shown in the figure, by comparing the UV absorption spectra of TPE-DPA solution and TPE-DPA solution filtered through a 0.22 um water membrane (TPE-DPA(+)), it is found that the UV absorption peak of TPE-DPA(+) disappears, indicating that TPE-DPA exists in the form of nano-aggregates in the solution. 2+ and TPE-DPA+1eq Cu 2+ The UV spectrum of Cu(+) has no obvious change, indicating that 2+ The addition of destroyed the nanoaggregates formed by TPE-DPA, causing the newly formed TPE-DPA-Cu to completely dissolve in water, resulting in little change in its UV absorption spectrum before and after filtration.

[0075] Example 8: Investigation of the Luminescence Properties of HA-TPE-DPA and TPE-DPA-C6

[0076] HA-TPE-DPA (3 k-10 k) was dissolved in DMSO and diluted with water to 1 μM (the system was 1% DMSO / 99% H2O). It was diluted 4, 16, 64, and 256 times with a mixed solvent of 1% DMSO / 99% H2O to prepare each sample. At the same time, TPE-DPA-C6 was prepared into a 1 μM sample (the system was 1% DMSO / 99% H2O), and then it was diluted 4, 8, 16, and 64 times with a mixed solvent of 1% DMSO / 99% H2O to prepare each sample. After each sample was placed for 15 min, the emission spectrum was measured in a fluorescence spectrometer with the following parameters: excitation wavelength 320 nm, emission wavelength: 400 nm-680 nm. The fluorescence intensity value at 460 nm was taken as a curve of change with concentration. The results are shown in Figure 8 As shown, from the comparison with the small molecule TPE-DPA-C6, it can be found that the polymer AIE copper ion detection material HA-TPE-DPA (3 k-10 k) at the same concentration has a stronger fluorescence value and a smaller CMC than the small molecule AIE copper ion detection material TPE-DPA-C6, indicating that the polymer AIE copper ion detection material can promote better aggregation of AIE molecules through additional forces, thereby presenting stronger fluorescence.

[0077] Example 9: Detection of Cu by HA-TPE-DPA and TPE-DPA 2+ Standard curve establishment

[0078] Dissolve CuCl2·2H2O in water to prepare a 10 mM stock solution, and dilute to a series of concentrations of 10, 20, 40, and 60 μM Cu. 2+ and 0.625, 1.25, 2.5, and 5 μM Cu 2+ Prepare a 200 μM sample of TPE-DPA (solvent system is 10% DMSO / 90% H2O) and mix with an equal volume of a series of concentrations of Cu 2+HA-TPE-DPA was prepared into a 100 μM sample (the solvent system was 10% DMSO / 90% H2O) and mixed with an equal volume of a series of concentrations of Cu 2+ After mixing the samples at 0, 0.625, 1.25, 2.5, and 5 μM, vortexing and placing them for 15 min, 100 μL of each concentration was added to a black 96-well plate (3 parallel wells) and the concentration of each Cu was determined by a multifunctional microplate reader. 2+ The fluorescence intensity at 460 nm was calculated for different concentrations of Cu 2+ Plot and perform linear fitting. The results are as follows Fig. 9 As shown, the detection of Cu based on TPE-DPA and HA-TPE-DPA 2+ The method is linear. 2+ In the detection method, the detection limit of TPE-DPA was 2.3141 μM, while the detection limit of HA-TPE-DPA probe was 0.1817 μM. The difference between the detection limits of the two was nearly 13 times, indicating that the polymer AIE copper ion detection material is effective for Cu 2+ Has higher sensitivity.

[0079] Example 10: HA-TPE-DPA is applied to the urine of copper-loaded rats 2+ Detection

[0080] After one week of adaptive feeding, the Wilson disease model rats were modeled using the copper loading method and fed with a diet containing 1.0 g / kg Cu2SO4 and water containing 0.185% Cu2SO4 for 10 weeks. The rats were free to eat and drink water every day. After the modeling was completed, the Wilson disease model rats were placed in a metabolic cage to collect 24 hours of urine. After the urine was shaken, the urine volume was accurately recorded. The collected 24-hour urine was filtered through a 0.45 μm filter membrane to remove suspended matter, diluted 100 times, and divided into two parts for HA-TPE-DPA and ICP-MS detection of Cu. 2+ The 24-hour urine copper content was calculated based on the recorded urine volume. 2+ The content method was as follows: HA-TPE-DPA was prepared into a 100 μM sample (the solvent system was 10% DMSO / 90% H2O) and mixed with an equal volume of urine diluent. Each sample was vortexed and placed for 15 min, and then 100 μL was added to a black 96-well plate. The fluorescence value at 460 nm (excitation wavelength: 320 nm) was measured by a multifunctional microplate reader. The Cu in urine was calculated based on the standard curve of urine copper content. 2+ The results are as follows Fig.10As shown in the figure, the detection results of HA-TPE-DPA are consistent with those of ICP-MS, and the 24-hour urine copper content calculated based on the recorded 24-hour urine volume is basically the same, indicating that the method based on HA-TPE-DPA for detecting urine copper has good accuracy and fast speed.

Claims

1. A copper ion detection kit, characterized in that: The invention comprises a copper ion detection material which is composed of a fluorophore, a recognition group with strong selective recognition ability for copper ions and a component containing or not containing a hydrophilic polymer material.

2. A copper ion detection kit, characterized in that: The invention comprises a copper ion detection material based on aggregation-induced luminescence, which is composed of a TPE group with aggregation-induced luminescence performance as a fluorophore, a recognition group with strong selective recognition ability for copper ions, and a component containing or not containing a hydrophilic polymer material, and has a structure shown in general formula I: General formula Ⅰ: Among them, the fluorophore TPE is ; X is -CH2-, -CH2OCO-, NH, -NHCO-, O, -OCO- or -CONH-; L is a linking group, including an alkylene group or an alkoxy group; G is a hydrophilic polymer material, including but not limited to the following polymers: hyaluronic acid, carboxymethyl chitosan, chondroitin sulfate, γ-polyglutamic acid, polyvinyl alcohol; R is a recognition group, which is generally an organic multidentate ligand that can coordinate with copper ions, and contains one of the coordination groups such as N, O, S, or any combination thereof.

3. The copper ion detection kit according to claim 2, characterized in that The fluorophore TPE of the copper ion detection material based on aggregation-induced luminescence is partially or completely replaced by -XR and -XLG, and has a structure shown in general formula II: General formula II: ; Wherein, R1, R2, R3, and R4 are optionally partially or completely replaced by -XR to form a small molecule AIE copper ion detection material; R1, R2, R3, and R4 are optionally replaced by -XLG, and the remaining positions are partially or completely replaced by -XR to obtain a polymer AIE copper ion detection material.

4. The copper ion detection kit according to claim 2, characterized in that The alkylene group is -(CH2) n -, alkenylene, alkynylene, cycloalkylene or heteroarylene, or any combination thereof, wherein the alkoxy group is -(CH2) n CO-、-(OCH2CH2O) n -、-(CH2CH2O) n -、-(OCH2CH2OCH2) n -、-(CH2CH2OCH2) n -、-(CH2CH2OCH2CH2) n - or any combination thereof, wherein n represents a natural number from 1 to 20.

5. The copper ion detection kit according to claim 2, characterized in that In the general formula I, R is a recognition group of copper ions, and its structural characteristics are as follows: General formula III: Wherein, Z is N or CH, and n represents a natural number from 0 to 20; R5 and R6 can be the same or different coordinating groups containing N, O, S electron donors, etc., or one can be H and the other can be a multidentate coordinating group, including but not limited to the following groups: 、 、 、 、 、 ; " ” represents the place where the substituent is attached.

6. The copper ion detection kit according to claim 2, characterized in that, The X is preferably -CH2- or -CONH-, and the hydrophilic polymer material G is preferably hyaluronic acid, carboxymethyl chitosan, or γ-polyglutamic acid.

7. The copper ion detection kit according to claim 3, characterized in that The R1, R2, R3, and R4 are preferably substituted with -XR to form a small molecule AIE copper ion detection material; optionally, R1, R2, R3, and R4 are substituted with -XLG, and preferably the trans isomer position is substituted with -XR to form a high molecular weight AIE copper ion detection material.

8. The copper ion detection kit according to claim 4, characterized in that: The alkylene group is preferably -(CH2) n -, the alkoxy group is preferably -(OCH2CH2O) n -、-(CH2CH2O) n -、-(OCH2CH2OCH2) n -、-(CH2CH2OCH2) n -、-(CH2CH2OCH2CH2) n - or any combination thereof, wherein n represents a natural number from 1 to 6.

9. The copper ion detection kit according to claim 5, characterized in that: The copper ion recognition group R is preferably the following group: 、 、 、 。 10. The copper ion detection kit according to claims 1-9, characterized in that: The application of the kit in copper ion detection includes, but is not limited to, clinical 24-hour urine copper detection, serum copper content detection, tissue copper content detection, cell copper content detection, and sewage copper content detection.

11. The copper ion detection kit according to claims 1-9, characterized in that: The application of the kit in copper ion detection includes but is not limited to the use of a multifunctional microplate reader, a fluorescence spectrometer, taking photos and identifying RGB according to the fluorescence color, and other application forms.

12. The copper ion detection kit according to claim 2-9, characterized in that: The preparation method of the copper ion detection material based on aggregation-induced luminescence is as follows: First, a carboxyl-containing TPE or a halogenated TPE is synthesized, and the TPE is reacted with the recognition group R through an amide reaction or a substitution reaction to obtain a small molecule AIE copper ion detection material; The carboxyl-containing TPE or the benzimidazole-substituted TPE is first connected to one end of the connecting group L and the recognition group R through an amide reaction, an esterification reaction or a substitution reaction, and then the other end of the connecting group L is modified on the hydrophilic polymer material G to obtain a polymer AIE copper ion detection material.

13. The copper ion detection kit according to claim 2-9, characterized in that: The copper ion detection material based on aggregation-induced luminescence has strong fluorescence emission in a high-water content system. When a detection sample containing copper ions is added, the recognition groups in the material coordinate with the copper ions to significantly increase their water solubility, destroy the nano-aggregate luminophores formed by the material, and cause a fluorescence change in the system. Quantitative detection of copper ions is achieved through the degree of fluorescence change.

Citation Information

Patent Citations

  • Copper ion fluorescent detecting probe and method for making same and purpose

    CN101261228A

  • Method for detecting bivalent copper ions and reagent kit

    CN103528969A

  • Method for continuously detecting Cu<2+> and pyrophosphate by aggregation-induced emission fluorescence sensing molecules

    CN106770133A

  • Organic compound for detecting metallic ion in water environment and application thereof

    CN108299396A

  • Fluorescent film for real-time detection of metal ions in water and preparation method of fluorescent film

    CN113185969A